PERAN UMKM TERHADAP PENINGKATAN PENDAPATAN PELAKU UMKM (STUDI KASUS DAERAH KECAMATAN SUNGAI KUNYIT) - Wiwik Sabani Wiwik Sabani; Okianna Okianna; Jumardi Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The number of micro, small and medium enterprises (MSMEs) in Indonesia is increasing, according to BPS data, including in the Mempawah Regency area. The Business Scale Data for MSMEs in West Kalimantan Province in 2021 showed that MSMEs in Mempawah Regency totaled 3,053 units. Thus, the number of MSME actors are also increasing, with the hope that after opening a MSME business, they can increase their income. This study was aimed to find out the role of micro, small and medium enterprises (MSMEs) in increasing the income of MSME actors in the Sungai Kunyit District, Mempawah Regency. The participants in this study were the MSME actors in the Sungai Kunyit District, Mempawah Regency, totaling 6 people. A case study was employed as the method of this study. Observation, interviews, and documentation studies were used as data collection techniques in this study. The results of the research and discussion indicated that MSME actors in the Sungai Kunyit District, Mempawah Regency experience changes in the income they get before and after starting a MSME business. The change is an increasing income. The increase in income is used to meet daily needs and other needs. In addition, it is also used to support the economy of the family of MSME actors.